Natural Fullerenes and Related Structures of Elemental Carbon - Rietmeijer, Frans J. M.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
Observational, experimental and analytical data show that C60, larger fullerenes, and related structures of elemental carbon exist in interstellar space, meteorites, and on Earth and are associated with meteorite in impact events and in carbon-rich environments such as coals (shungite) and bitumen. The existence of natural fullerenes is at best contested and incompletely documented; realistically it is still controversial. Their presence in astronomical environments can be experimentally constrained but observationally they remain elusive. Fullerenes formation in planetary environments is poorly understood. They survived for giga-years when the environmental conditions were exactly right but even then only a fraction of their original abundance survived. Natural fullerenes and related carbon structures are found in interstellar space, in carbonaceous meteorites associated with giant meteorite impacts (including at the Cretaceous-Tertiary boundary) as well as in soot, coal and natural bitumen. This book provides an up-to-date summary of the state of knowledge on natural fullerenes occurrences and the laboratory techniques used to determine their presence at low concentration in rock samples. It demonstrates that natural fullerenes exist and should be searched for in places not yet considered such as carbon-containing deep-seated crustal rocks. Natural Fullerenes and Related Structures of Elemental Carbon is written for professional astronomers, meteoriticists, earth and planetary scientists, biologists and chemists interested in carbon and hydrocarbon vapor condensation. It is an invaluable resource for practicing research scientists and science teachers in Earth and Planetary Science, Astronomy and Carbon Science.
Introduction: Space - Pandora's Box -- Formation of Fullerenes -- Carbonaceous Onion-Like Particles: A Possible Component of the Interstellar Medium -- Fullerenes and Related Carbon Compounds in Interstellar Environments -- Natural C60 and Large Fullerenes: A Matter of Detection and Astrophysical Implications -- Fullerenes in Meteorites and the Nature of Planetary Atmospheres -- Fullerenes and Nanodiamonds in Aggregate Interplanetary Dust and Carbonaceous Meteorites -- Fullerenes and Related Structural Forms of Carbon in Chondritic Meteorites and the Moon -- Fullerenes in the Cretaceous-Tertiary Boundary -- Fullerene C60 in Solid Bitumen Accumulations in Neo-Proterozoic Pillow-Lavas at Mítov (Bohemian Massif) -- Fullerene Synthesis by Alteration of Coal and Shale by Simulated Lightning -- Fullerene in Some Coal Deposits in China -- Biogenic Fullerenes -- Future Procedures for Isolation of Higher Fullerenes in Natural and Synthetic Soot.
Keywords: CHEMISTRY; CHEMISTRY, PHYSICAL ORGANIC; LIFE SCIENCES; GEOCHEMISTRY; PLANETOLOGY; ASTRONOMY; PLASMA (IONIZED GASES).; CHEMISTRY; PHYSICAL CHEMISTRY; GEOCHEMISTRY; ASTRONOMY, ASTROPHYSICS AND COSMOLOGY; PLANETOLOGY; ATOMS, MOLECULES, CLUSTERS AND PLASMAS; BIOGEOSCIENCES